The Effects of Social Support, Participation in Supporting Network Communities and Stigma and Discrimination of Surrounding Environment against Self-Stigma on Housewives PLWHA in Special Region of Yogyakarta - Dyah Pradnya Paramitha (Alma Ata University Press, 2018)
As many as 76% of HIV/AIDS cases in Special Region of Yogyakarta are transmitted through sexual contact. This condition affects 407 housewives who are infected with HIV from their husbands. The feeling of anxiety, anger, and disappointment felt by HIV/AIDS sufferers, medical care, discrimination, and public response to this disease often leads to people living with HIV/AIDS (PLWHA) are living in anxiety, stress, depression, and lack of social support so that people tend to avoid or withdraw from their environment. Therefore, in the end, this causes only a small number of people living with HIV/AIDS (PLWHA) who can access the health services for ARV therapy. This research method is analytical descriptive with cross-sectional approach which aims to analyze the factors that influence self-stigma on housewives PLWHA in Special Region of Yogyakarta. Bivariate analysis used was chi-square analysis whereas the multivariate analysis used was logistic regression. The result shows that social support is the most dominant factor influencing self-stigma. It is advisable for the government to improve the provision of social support to people living with HIV/AIDS (PLWHA) by providing care and treatment services that are easily accessible and appropriate to the needs of PLWHA as well as educate the public properly about HIV/AIDS raising awareness of PLWHA without discrimination. Key words: Self-Stigma , PLWHA (people living with HIV/AIDS)